Numerical modelling of surface subsidence induced by underground coal gasification - Yury, Derbin (2019)
Underground coal gasification (UCG) is an alternative method of energy extraction from coal. This method has significant advantages over traditional coal mining. Because the coal is combusted in situ, there is no need for underground labour and the environmentally unfriendly products of burning remain underground. The method can be applied to the coal seam of poor quality and deep underground where traditional mines would not be profitable. Although the method has been known for a century, there are only a few projects that exist on an industrial scale. One of the obstacles of UCG implementation is surface subsidence, which can damage infrastructure, UCG equipment and boreholes. To organize UCG in the most efficient way, the surface subsidence should be predicted.